A novel design of 4-Gbps and 6-Gbps IR-UWB pulse generator - Al-Khateeb, Khalid A. Saeed; Mohammed, Ahmed R. (2011)
A novel design of 4-Gbps and 6-Gbps Impulse Radio Ultra Wide band (IR-UWB) pulse generator for short range wireless communication is presented. The simple structure of the proposed pulse generator helps to overcome the limitations of generating the two high speeds, the pulse generator based on two synchronized sources of 2GHz only. The pulse generation technique support transmission of 250ps pulses with immunity on pulse overlapping. The spectrum of the generated pulses complies with the Federal Communication Commission (FCC) UWB frequency mask requirements for indoor and outdoor. A combination of two modulation schemes has been used to increase the system throughput, Bi-Phase Modulation (BPM) and On-Off Keying.